Biplot Analysis for Spatial Mapping of Dengue Hemorrhagic Fever (DHF) Incidence in Indonesia - Gani, Fadjryani Abdul; Aisya, Cici; Ainanur; Afriza, Dini Aprilia (Program Studi Matematika, Universitas Tadulako, 2024)
Dengue Hemorrhagic Fever (DHF) is a serious threat to Indonesian public health, with the dengue virus spread by the Aedes aegypti mosquito continuing to claim victims in all provinces in Indonesia. The drastic variation of DHF incidence between provinces requires an in-depth understanding of its distribution pattern. Biplot analysis allows researchers to identify patterns based on factors that influence the incidence of DHF in different provinces. This study aims to identify the spatial distribution pattern of DHF in Indonesia using biplot analysis, an approach that allows complex visualization of factors affecting DHF incidence. Results showed that 62.48% of the data variation could be explained through biplot representation, revealing spatial distribution patterns, proximity between objects and diversity between variables. Key findings include the identification of provinces with the highest DHF cases (56,388 cases) in quadrant IV, the high incidence of DHF cases was associated with similar characteristics of average air humidity. In addition, there was significant variation in the number of DHF cases between provinces indicating disparities in the number of DHF cases in different parts of Indonesia, as well as relative uniformity in the percentage of households with proper sanitation (descriptive average of 86.62%). The results of this study are expected to assist policy makers in formulating more effective and targeted dengue prevention and control strategies, potentially reducing the incidence of dengue and improving the health of the Indonesian people.